The legal interfaces of urban planning in risk areas of Aracaju, SE - Meneses, Fernanda Alves Góis; Costa , Jailton de Jesus; Araújo, Rozana Rivas de; Oliveira, Ingrid Carvalho Santos; Souza, Rosemeri Melo e (National Journal of City Management, 2024)
The objective of this study was to analyze the National Policy of Civil Protection and Defense – PNPDEC (Law No. 12,608/2012) and Urban Policy as urban planning instruments for disaster risk reduction at the municipal level, with the purpose of understanding the various interactions among land use characteristics, public policies, and disaster risks. The research consisted of a literature review, based on data collection from existing legislation, as well as official publications produced by government agencies and bodies in support of Civil Protection and Defense, as well as at the municipal level. The municipality of Aracaju (SE) was considered as a case study, particularly the Jabotiana neighborhood, which, due to the intensification of urbanization in the last two decades (2000-2020), has been experiencing a serious socio-environmental problem that, coupled with the inefficiency of sanitation, has favored the occurrence of floods. It is noted that the most vulnerable segment of the population suffers the consequences of such events with greater intensity, due to their lower capacity to cope with disasters compared to the more affluent population, since the latter may inhabit the safer parts of the city, less exposed to risks. These conditions result from the lack of restriction through the Urban Development Master Plan (PDDU), which is outdated and incompatible with the urban reality of Aracaju, and from irregular and precarious occupation in Risk Areas and Permanent Preservation Areas.